PENERAPAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI SRATEN - Ali Ikhsani; Erlina Prihatnani (Universitas Negeri Medan, 2017)
The purpose of research is can improve the learning result of Science material of plant structure in fourth grade students. In this research used the method of Make A Macth as an alternative used in the science learning of plant structure material. This type of research is Classroom Action Research. The subjects of this study are the students of class level IV which amounted to 21 students. The study was conducted in 2 part, each part consisting of planning, implementation, observation and reflection. Research of Make A Macth method can improve the learning result of Science material of plant structure in fourth grade students of SD Negeri Sraten 01 Tuntang Sub-district Semarang Regency Lesson Year 2017/2018. Evidence of an increase in Science learning outcomes is the percentage of learning outcomes from part I to part II of 19%. In the first part students who complete 15 students or 71% and students who have not completed 6 students or 29% with an average of 72. In part II students who completed 19 students or 90% and students who have not completed 2 students or 10% with an average of 81. Keyword: Learning Outcomes, Make A Macth, Plant Structure Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa melaluhi pembelajaran kooperatif tipe Make A Macth dengan media gambar dapat meningkatkan hasil belajar IPA. Dalam penelitian ini, peneliti menggunakan metode Make A Macth sebagai alternatif yang digunakan dalam pembelajaran IPA materi struktur tumbuhan. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Subyek penelitian ini adalah siswa kelas IV yang berjumlah 21 siswa. Penelitian dilaksanakan dalam 2 siklus yang setiap siklusnya terdiri dari perencanaan, pelaksanaan, pengamatan dan refleksi. hasil penelitian metode Make A Macth dapat meningkatkan hasil belajar IPA materi struktur tumbuhan pada siswa kelas IV SD Negeri Sraten 01 Kecamatan Tuntang Kabupaten Semarang Tahun Pelajaran 2017/2018. Bukti adanya peningkatan hasil belajar IPA adalah persentase hasil belajar dari siklus I ke siklus II sebanyak 19%. Pada siklus I siswa yang tuntas 15 siswa atau 71% dan siswa yang belum tuntas 6 siswa atau 29% dengan rata-rata 72. Pada siklus II siswa yang tuntas 19 siswa atau 90% dan siswa yang belum tuntas 2 siswa atau 10% dengan rata-rata 81. Kata Kunci: Hasil belajar, Make A Macth, Struktur Tumbuhan